Predictors of Cardiogenic Shock During or After Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome - Thipsawat, Sopida; Pensri, Laddawan; Poonsong, Crisaporn (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Cardiogenic shock is a severe and life-threatening condition. This study aimed to investigate the predictors of cardiogenic shock during or after percutaneous coronary intervention in patients with acute coronary syndrome. Methods This paper was a retrospective cohort study that analyzes secondary data from the main research project on the prevalence of bleeding and the analysis of relationship predictors for bleeding in patients with acute coronary syndrome after percutaneous coronary intervention. The sample group consisted of 295 patients with acute coronary syndrome who underwent percutaneous coronary intervention at a secondary hospital. Data analysis was performed using binary logistic regression. Results The study found that 134 patients with acute coronary syndrome during hospitalization, representing 45.4%, developed cardiogenic shock during or after percutaneous coronary intervention (PCI). Factors that predicted the occurrence of cardiogenic shock during or after PCI were cardiogenic shock before PCI (adjusted OR = 8.44, 95% CI: 4.09–17.40), arrhythmias (adjusted OR = 2.09, 95% CI: 1.17–3.71), and procedure time (adjusted OR = 1.02, 95% CI: 1.00–1.03). Conclusion and Recommendations The study results indicate that if the occurrence of cardiogenic shock before percutaneous coronary intervention and arrhythmias can be prevented, as well as if procedure time can be reduced, this may help decrease the incidence of cardiogenic shock during or after percutaneous coronary intervention.